Accumulation of PBDEs and MeO-PBDEs in notothenioid fish from the South Shetland Islands, Antarctica: An interspecies comparative study - Rios, Juan Manuel; Mammana, Sabrina Belén; Moreira, Eugenia; Poma, Giulia; Malarvannan, Govindan; Barrera Oro, Esteban; Covaci, Adrian; Ciocco, Nestor Fernando; Altamirano, Jorgelina Cecilia (Marine Pollution Bulletin)
Concentrations of polybrominated diphenyl ethers (PBDEs) and methoxylated polybrominated diphenyl ethers (MeO-PBDEs); are reported in specimens of fish notothenioids Chaenocephalus aceratus (SSI), Trematomus bernacchii (ERN), and Nototheniops nudifrons (NOD) from the South Shetland Islands, Antarctica. Significant differences in the accumulation of 2′-MeO-BDE-68 and 6-MeO-BDE-47 were detected among the analysed species. MeO-BDEs were significantly higher in SSI (11.7, 8.6, and 14.1 ng g−1 lw) than in NOD (1.63, 1.63, and 3.0 ng g−1 lw) in muscle, liver, and gill, respectively. Feeding ecology traits explain the accumulation patterns of MeO-PBDEs. SSI has a higher feeding activity with a broader diet, followed by ERN, whereas NOD is a benthic/sedentary fish with a narrower diet. The accumulation of PBDEs was neither species-, nor tissue-specific. The current study expands the knowledge concerning the accumulation of PBDEs and MeO-PBDEs in Antarctic marine fish and supports the importance of species-specificity in the accumulation of MeO-PBDEs. Fil: Rios, Juan Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto de Medicina y Biología Experimental de Cuyo; Argentina Fil: Mammana, Sabrina Belén. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; ...